Effect of different obturation techniques on treatment results in single-visit non-surgical endodontic retreatment: randomized controlled clinical study - Merve Işık; Zeliha Uğur Aydın (BMC, 2024)
Abstract Background Evaluating the effect of different obturation techniques on postoperative pain level and radiographic healing on non-surgical endodontic retreatment (NSER) applied in a single visit in teeth with a single root canal and apical periodontitis (AP). Materials and methods Sixty-three teeth from 50 systemically healthy patients (mean age 34.19 ± 9.75 years; 27 women, 23 men) were included in the study. Residual root canal filling materials were removed. All teeth were randomly divided into three groups according to the obturation technique: cold lateral compaction (CLC), continuous wave compaction (CWC), and thermoplasticized gutta-core (TGC). Pain status was evaluated using the Numerical Pain Rating Scale (NRS) in all cases. Periapical index (PAI) scores were recorded in preoperative and postoperative 6-month on the periapical radiographs. Data were analyzed as statistically (IBM, Armonk, NY, USA). The significance level was determined as p < 0.05. Results It was found that more postoperative pain occurred in the 3rd-hour interval after CLC and CWC compared to the 7th-day interval (p < 0.05). There was no difference in postoperative pain between obturation techniques in all evaluated time intervals (p > 0.05). There was no difference in the PAI scores recorded at six months between obturation techniques for all periods (p > 0.05). Similar radiographic improvement was observed in all obturation techniques at 6-months (p > 0.05). Conclusion CLC, CWC, and TGC root canal obturation techniques were found to have similar efficacy after NSER in a single visit in teeth with AP at six months. Trial registration The research was retrospectively registered on the website www.clinicaltrials.gov with the registration number NCT06226740 on 26/01/2024.